2023
DOI: 10.1111/ejn.16105
|View full text |Cite
|
Sign up to set email alerts
|

Influences of local and global context on local orientation perception

Jinfeng Huang,
Yifeng Zhou,
Tzvetomir Tzvetanov

Abstract: Visual context modulates perception of local orientation attributes. These spatially very localised effects are considered to correspond to specific excitatory–inhibitory connectivity patterns of early visual areas as V1, creating perceptual tilt repulsion and attraction effects. Here, orientation misperception of small Gabor stimuli was used as a probe of this computational structure by sampling a large spatio‐orientation space to reveal expected asymmetries due to the underlying neuronal processing. Surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…V1 neurons receive visual information from a specific range of the retina, the classical receptive field (CRF), via the lateral geniculate nucleus (LGN), and the collection of feedforward input within the CRF largely determines the neuron's firing pattern. As the size of the visual stimulus increases, the portion outside of the CRF can also affect and generally attenuates neuronal firing activity, known as 'surround suppression' (Huang et al, 2023;Nienborg et al, 2013;Orekhova et al, 2020;Wang et al, 2009). Biological experiments have demonstrated that gamma oscillations are significantly modulated by size, namely, the oscillatory power in each frequency band increases with the most pronounced changes in the low gamma range (30-80 Hz) as stimulus size is increased, and the peak frequency of gamma oscillation decreased monotonically with increasing stimulus size (Gieselmann & Thiele, 2008;Jia et al, 2011;Ray & Maunsell, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…V1 neurons receive visual information from a specific range of the retina, the classical receptive field (CRF), via the lateral geniculate nucleus (LGN), and the collection of feedforward input within the CRF largely determines the neuron's firing pattern. As the size of the visual stimulus increases, the portion outside of the CRF can also affect and generally attenuates neuronal firing activity, known as 'surround suppression' (Huang et al, 2023;Nienborg et al, 2013;Orekhova et al, 2020;Wang et al, 2009). Biological experiments have demonstrated that gamma oscillations are significantly modulated by size, namely, the oscillatory power in each frequency band increases with the most pronounced changes in the low gamma range (30-80 Hz) as stimulus size is increased, and the peak frequency of gamma oscillation decreased monotonically with increasing stimulus size (Gieselmann & Thiele, 2008;Jia et al, 2011;Ray & Maunsell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous physiological experiments and modelling studies have answered this question using firing rates as an entry point. Experimental evidence suggests that size modulation effects may be contributed by feedforward connections, longrange horizontal connections within cortical areas and feedback connections between different areas of the cortex within the primary visual cortex at different spatiotemporal scales and stimulus properties (Angelucci et al, 2017;Huang et al, 2023;Nurminen et al, 2018;Ozeki et al, 2004;Sato et al, 2014). Modelling studies similarly emphasize the role of feedforward, feedback, lateral connections and other special circuits (Di Santo et al, 2022;Keller et al, 2020;Li & Young, 2021;Schwabe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%